Stability of a Mixed Type Functional Equation on Multi-Banach Spaces: A Fixed Point Approach - Wang, Liguang; Liu, Bo; Bai, Ran (Fixed point theory and applications (Hindawi Publishing Corporation), 2010)
Using fixed point methods, we prove the Hyers-Ulam-Rassias stability of a mixed type functional equation on multi-Banach spaces.